Perbandingan Kandungan Fenolik dan Aktivitas Antioksidan pada Varian Seduhan Teh dan Varian Teh Kombucha Secara Spektrofotometri Visible - Maghfirah , Dini; Pulungan , Ainil Fithri; Ridwanto, Ridwanto; Yuniarti , Rafita (Journal of Pharmaceutical and Sciences, 2025)
One of the most widely consumed aromatic beverages in the world is tea. Tea shoots are rich in polyphenolic compounds that function as antioxidants. Not many people know that tea can be fermented with a type of bacteria and yeast culture that can be consumed as a drink for health known as kombucha tea. The health benefits of consuming kombucha tea as anti-carcinogenic, anti-diabetic, detoxification, increased immune response, treating stomach ulcers and lowering cholesterol levels as well as high blood pressure. The purpose of this study was to determine the total phenolic content and antioxidant activity as well as the comparison of total phenolic content and antioxidant activity in tea brewing variations with kombucha tea variations. The methods carried out include testing the total phenolic content and antioxidant activity using the DPPH method on tea brewing variants and kombucha tea variants by visible spectrophotometry.mThe results of total phenolic content in black tea, green tea, and oolong tea were 24,480 mgGAE/g, 26,538 mgGAE/g, and 38,427 mgGAE/g, respectively, while kombucha black tea, green tea, and oolong tea were 39,264 mgGAE/g, 58,581 mgGAE/g, and 64,299 mgGAE/g, respectively. Brewed black tea, green tea, and oolong tea have antioxidant activity with IC50 values of 105,68 ppm in teh moderate category, 81,59 ppm in teh strong category, and 56,25 ppm in the strong category, respectively. In kombucha black tea, green tea, and oolong tea have antioxidant activity with IC50 values respectively 101,60 ppm with moderate category, 55,82 ppm with strong category, and 39,69 ppm with very strong category. While teh vitamin C comparator has antioxidant activity with an IC50 value of 3,22 ppm with a very strong category.